1956
DOI: 10.1039/jr9560003948
|View full text |Cite
|
Sign up to set email alerts
|

769. Magnetic properties of some metal carboxylates

Abstract: The paramagnetic susceptibilities of khe anhydrous stearates and laurates of nickel, cobalt, and iron and of copper stearate are reported. Results are included for the hydrated forms of cobalt and nickel laurates. Measurements a t five different temperatures in the range 105-333" K show that only the copper carboxylates fail to obey a Curie-Weiss law. The magnetic moments of the ferric compounds, however, are anomalously low, and the Weiss constant 8 is very large.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1961
1961
2002
2002

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Copper salts of carboxylic acids adopt a structure in which two copper atoms are bridged by four carboxylate groups, as in copper acetate ͑van Niekerk and Schoening, 1953͒. A similar structure has been proposed for copper palmitate and stearate ͑Herron and Pink, 1956;Stommen et al, 1987͒. Therefore the copper soaps are quite different from the zinc and lead soaps, which would explain why they divert from the trend observed for the latter.…”
Section: Resultsmentioning
confidence: 90%
“…Copper salts of carboxylic acids adopt a structure in which two copper atoms are bridged by four carboxylate groups, as in copper acetate ͑van Niekerk and Schoening, 1953͒. A similar structure has been proposed for copper palmitate and stearate ͑Herron and Pink, 1956;Stommen et al, 1987͒. Therefore the copper soaps are quite different from the zinc and lead soaps, which would explain why they divert from the trend observed for the latter.…”
Section: Resultsmentioning
confidence: 90%
“…From IR, UV and magnetic susceptibility results, he concluded that the red dihydrate and blue anhydrate are octahedral and tetrahedral complexes, respectively, whose structure formulas are proposed by Harron and Pink. 21 Namely, the red hydrate is in an octahedral structure coordinated with two carboxylate ions and two aqua ligands, while the blue anhydrate 1s m a tetrahedral structure co- ordinated with two carboxylate ions. The pink Co(II) stearate had a chemical composition nearer to the red dihydrate than the blue anhydrate but its composition was somewhat indefinite.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of this intermediate a Total BzOH added to the system including the initial charge, make-up, and acid combined with the catalyst. 6 Calculated from CO2 value assuming 05 = 2002. c Primarily PhCOOPh with some PhOPh. For ease of calculation, all of former assumed.…”
Section: ó Industrial and Engineering Chemistrymentioning
confidence: 99%